HUBUNGAN REAKSI EMOSIONAL MAHASISWA SEMESTER PERTAMA DENGAN TINGKAT KELULUSAN PRAKTIKUM ANATOMI BERBASIS CADAVER - Ayu Febriyanti Abbas; Vebiyanti Tentua; Johan B. Bension; Parningotan Y. Silalahi; Sherly Yakobus; Irwan Irwan (Fakultas Kedokteran Universitas Pattimura, 2021)
Emotion is psychological condition that supports a person to make or do something after a stimulus originating from within and outside him/her. First-year medical students habitually experience various emotional reactions and mixed feelings, when they got cadaver for the first time in the practicum room or surgery room. Based on data graduation got from the Medical Education Unit (MEU) of the Faculty of Medicine at Pattimura University, the level of effectiveness of anatomy subject from the 2014/2015 academic year to the 2016/2017 only reached 53,63% this figure shows that a small number of students are capable pass anatomy sub-alignment course. This research aims to describe the emotional reaction of the first semester students with a graduation level of cadaver-based anatomy practicum. This research is a quantitative analytic research with sectional approach. Amount of 142 respondent were obtained using total sampling for the all 2019 first semester students who participated in the second biomedical anatomysub-block of the 2019/2020 Academic Year. Retrieval of data using the cadaver student's emotional reaction dealing with questionnaire that has been validated. Based on the result of the study found that a mount of 31,2% of students who passed the anatomy practicum experience got the positive emotions, while 25% felt negative emotions. Then 68,8% and 80% of student who experienced positive and negative emotions were stated didn’t pass the test. These results showed that there was no correlation between emotional reactions and cadaver-based anatomical practicum graduation rates, with the calculated Chi Square amount=0.069 and p=0,793 at the significance of 0,050. So it can be concluded that there is no relationship between emotional reactions with the graduation level of cadaver-based anatomical practicum in 2019 first semester students of the Faculty of Medicine, Pattimura University.